Analysis of the Seismic Performance of a Two-Span Specially Shaped Column Frame. (18th July 2019) - Teng, Zhen-chao; Zhao, Tian-jia; Liu, Yu
Abstract : In traditional building construction, the structural columns restrict the design of the buildings and the layout of furniture, so the use of specially shaped columns came into being. The finite element model of a reinforced concrete framework using specially shaped columns was established by using the ABAQUS software. The effects of concrete strength, reinforcement ratio, and axial compression ratio on the seismic performance of the building incorporating such columns were studied. The numerical analysis was performed for a ten-frame structure with specially shaped columns under low reversed cyclic loading. The load-displacement curve, peak load, ductility coefficient, energy dissipation capacity, and stiffness degradation curve of the specially shaped column frame were obtained using the ABAQUS finite element software. The following three results were obtained from the investigation: First, when the strength of concrete in the specially shaped column frame structure was increased, the peak load increased, while the ductility and energy dissipation capacity weakened, which accelerated the stiffness degradation of the structure. Second, when the reinforcement ratio was increased in the specially shaped column frame structure, the peak load increased and the ductility and energy dissipation capacity also increased, which increased the stiffness of the structure. Third, when the axial compression ratio was increased in the structure, the peak load increased, while ductility and energy dissipation capacity reduced, which accelerated the degradation of structural stiffness.